Utilization of community healthcare services and family caregivers’ needs for support. A survey of family caregivers for older, home-dwelling persons with dementia in Northern Norway - Moholt, Jill-Marit (UiT The Arctic University of Norway, 2019)
In line with the current aging policies, the majority of older persons with dementia live in their own home. Although a range of community healthcare services is available to support home-dwelling persons with dementia, informal care provided by family caregivers constitutes a major portion of the care provided. This study contributes to knowledge regarding the use and nonuse of community healthcare services in families in which an older, home-dwelling person has dementia. A central aspect of the study was to illuminate the utilization of community healthcare services with regard to the estimated needs of the family caregivers. The study has a cross-sectional design, and a survey was administered to family caregivers of older, home-dwelling persons with dementia in Northern Norway (n = 430). Overall, the majority of the families used one or more homebased services, but services that can serve as respite care for family caregivers were utilized to a limited extent. The amount of service use may indicate unintended variations in access to and use of services within demographic and socioeconomic subgroups, contrary to welfare state policy aims. Reasons for non-use of services were multifaceted and complex, and were related to attributes of the person with dementia, the family caregivers and the healthcare services. Although services were unused, several family caregivers reported substantial needs for the services. The study indicates that family caregivers contribute substantially to caring for home-dwelling people with dementia. Family caregivers should receive formal help and support based on their own needs, and family caregiver assessment should be a priority area within community dementia care. As part of this study, we made available a Norwegian version of the COPE Index, which is a first-stage assessment tool that can be adapted and used among healthcare professionals to detect family caregivers in need of support from community healthcare services.